Quality of Life after Rhinoplasty: A Prospective Study - Papadopulos, Nikolaos A.; Liebmann, Janina; Kloeppel, Markus; Henrich, Gerhard; Machens, Hans-Günther; Staudenmaier, Rainer; Niehaus, Richard (Facial Plastic Surgery, 2021)
As our previous studies have shown, cosmetic surgery has a positive correlation with postoperative well-being. The aim of this study was to prospectively examine the postoperative changes in quality of life (QoL) after a rhinoplasty. Thirty-four patients who underwent septorhinoplasty performed by a single surgeon from July 2015 to October 2018 reported in indication-specific self-developed and different validated questionnaires (FLZM or Fragen zur Lebenszufriedenheit Module, Freiburg Personality Inventor, Rosenberg self-esteem scale, Functional Rhinoplasty Outcome Inventory 17 [FROI-17], and Glasgow Benefit Inventory [GBI]) on the status of their QoL preoperatively (T0) and 6 months' follow-up (T1). Our goal was to assess the difference in psyche and self-esteem and to get objective insights into the effect of the operation. Significant improvements in QoL in terms of general module, health, and appearance were noted. The general part of the FLZM showed increasing T1 values in the sum scores (p = 0.005). With regard to the item “health,” T1 was better than the norm data (p = 0.003). The statistically significant improvement for the item nose appearance (p < 0.0001) after operation and T1 versus reference data (p < 0.010) should be highlighted. The subjective patient ratings showed statistically significant T1 improvements for all items of the FROI-17: overall nose (p < 0.0001), nasal function (p = 0.001), general/further symptoms (p = 0.006), and confidence increased by aesthetic changes (p < 0.0001). Furthermore, the GBI score shows an improved QoL after rhinoplasty (p < 0.0001). Based on the assessment of a variety of disease- and nondisease-specific validated questionnaires, numerous improvements in the QoL of the patients were observed. Therefore, we support septorhinoplasty as a meaningful procedure regarding QoL improvement. The level of evidence is Level II prospective cohort study.
Keywords: rhinoplasty; nose; quality of life; aesthetic surgery; patient satisfaction